2020
DOI: 10.1186/s12879-020-05512-7
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of tuberculosis-associated hyperglycemia in individuals newly screened for type 2 diabetes mellitus: systematic review and meta-analysis

Abstract: Background There is scarce evidence that tuberculosis (TB) can cause diabetes in those not previously known to be diabetic. Whilst the World Health Organization (WHO) recommends screening for Diabetes Mellitus (DM) at the onset of TB treatment, nevertheless, it remains to be elucidated which patients with TB-associated hyperglycemia are at higher risk for developing DM and stand to benefit from a more regular follow-up. This review aims to firstly quantify the reduction of newly detected hyperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Therefore, transient hyperglycaemia could spuriously increase the prevalence of DM. Nonetheless, hyperglycaemia does not resolve at follow-up in 50% of people with TB and hyperglycaemia at baseline 84 . More studies are needed to determine whether transient hyperglycaemia in TB heralds new onset DM or predicts future risk for DM.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, transient hyperglycaemia could spuriously increase the prevalence of DM. Nonetheless, hyperglycaemia does not resolve at follow-up in 50% of people with TB and hyperglycaemia at baseline 84 . More studies are needed to determine whether transient hyperglycaemia in TB heralds new onset DM or predicts future risk for DM.…”
Section: Discussionmentioning
confidence: 98%
“…The association between TB and DM is well known; however, data are conflicting on the direction of the relationship. Diabetics are 1.5 to 3 times more likely to develop active TB [ 63 , 64 ]. Conversely, a meta-analysis by Menon et al [ 65 ] showed that up to 50% of people diagnosed with TB had hyperglycemia at baseline, which remained unresolved in over 10% of cases even after 6 months of effective anti-TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with active TB, defined as a positive Xpert MTB/ RIF, positive Mycobacterium tuberculosis culture, or individuals currently taking TB therapy at the time of study enrollment, were excluded from this analysis. We excluded those with active TB because active disease may result in stress hyperglycemia [19], and our work focuses on the effect of prior TB on the risk of future dysglycemia. We also excluded participants with active cancer or autoimmune diseases and those who reported taking anti-epileptic or glucocorticoid medications because these conditions and therapies can affect hemoglobin A1c.…”
Section: Study Definitionsmentioning
confidence: 99%